Kombinasi Metode Pembobotan Rank Reciprocal dan TOPSIS dalam Seleksi Penerimaan Staff IT - Muhammad Najib Dwi Satria; Ade Surahman (CV. Keranjang Teknologi Media, 2024)
The selection of IT staff recruitment is a critical stage in forming a competent team and in accordance with the needs of the organization in the era of information technology that continues to grow. This process involves an in-depth evaluation of the prospective employee's technical skills, work experience, and interpersonal abilities. One of the problems that occurs is a lack of technical skills that match the specific needs of the company or project. In addition, intense competition in the IT industry often leads to difficulties in finding candidates who meet the criteria with high qualifications. With this study, it will provide recommendations in the IT staff recruitment selection process by applying the reciprocal rank weighting method for criteria weighting and the TOPSIS method for the IT staff recruitment selection process which will produce rankings in the IT staff recruitment selection. The ranking results showed that the final results of candidate Fransiska with a total value of 0.791 got rank 1, candidate Fandi with a total value of 0.5366 got rank 2, candidate Arini with a total value of 0.533 got rank 3.